Study on internal labor migration in Vietnam (2015-2020) - Trong, Dinh Van; Tho, Pham Duc; Trinh, Nguyen Thi Kieu; Thuy, Tran Thi Thanh; Hà, Nguyễn Thế (Edelweiss Applied Science and Technology, 2025)
To elucidate the issue of "Internal Labor Migration in Vietnam during the period of 2015-2020," utilizing data collected from Vietnamese national archives and national information portals, and through a historical approach, the research team employed synthesis, analysis, and comparative methods to clarify the factors influencing internal labor migration in Vietnam, as well as the status of internal labor migration from 2015 to 2020. Additionally, the team utilized a logical approach to provide certain exchanges and discussions on internal labor migration in Vietnam during this period. The research results of this study aim to contribute, albeit modestly, to the body of knowledge elucidating the process of internal labor migration in Vietnam during the period of 2015-2020. This material holds valuable data for those researching internal labor migration in Vietnam in the future.